A retrospective study on palmoplantar psoriasis and its associations in a tertiary care centre - Perumal, Saradha K.; Gopinath, Sudha R. (International Journal of Research in Dermatology, 2019)
Background: Psoriasis is a chronic immune mediated inflammatory condition of the skin. Palmoplantar psoriasis (PPP) is a clinical variant of plaque psoriasis affecting palms and soles extending to the wrist and the margins of the soles and heels. This study was done to find out the prevalence of palmoplantar psoriasis in our setting. The aim of the study was to determine the prevalence, demographic features and other co-morbidities of the palmoplantar plaque psoriasis in a tertiary care centre. Methods: We conducted retrospective study for a period of one year (January 2017 to December 2017) on palmoplantar plaque psoriasis patients attending the dermatology OPD. Results: Among 552 enrolled psoriasis patients, 85 were clinically diagnosed to have palmoplantar psoriasis. The mean age of the patient was 45 years. Most of them belong to 4th, 5th and 6th decade of life. The male to female ratio was 1:2.26. The duration of the disease was more than one year in 73% of patients at the study time. Occupation of the patients included house-wives (50%), manual labourers (36%) and office goers, (13%). Hyperkeratotic plaque type psoriasis with scaling and fissures was the predominant morphological pattern recorded. Dyslipidemia (22%), overweight and obesity (56%), hypothyroidism (6%) and diabetes mellitus (12%) were the observed co-morbidities in this study. Conclusions: The prevalence of palmoplantar psoriasis (0.09%) was low in our study. Palmoplantar psoriasis affected middle aged adults and had a female predominance in this study. Overweight, obesity, dyslipidemia, diabetes mellitus and hypothyroidism were the co-morbid conditions observed in this study. Being a relapsing and chronic condition the disease poses a poor quality of life than plaque type psoriasis.